2021
DOI: 10.3390/cells10092423
|View full text |Cite
|
Sign up to set email alerts
|

COL5A1 RS12722 Is Associated with Temporomandibular Joint Anterior Disc Displacement without Reduction in Polish Caucasians

Abstract: Numerous reports describe the association between the single-nucleotide polymorphism (SNP) rs12722 and rs13946 in the COL5A1 gene and injuries, such as Achilles tendon pathology, anterior cruciate ligament (ACL) injuries, and tennis elbow. Hence, there were no studies investigating COL5A1 and temporomandibular joint (TMJ) pathology. The aim of this study is to evaluate the relationship between COL5A1 rs12722 and rs13946 SNPs and TMJ articular disc displacement without reduction (ADDwoR). In this case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…These results have confirmed the findings of another study demonstrating that older adults have thicker MS capsules [ 11 ]. Moreover, these findings are consistent with those of some studies that highlighted the role of the collagens in various diseases and tissues [ 21 , 22 , 23 ]. Parkes et al [ 21 ] reported the prominent role of collagen and HA in the ECM of ovaries, suggesting their crucial activity for ovarian homeostasis, possibly through signaling events or tissue micromechanism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results have confirmed the findings of another study demonstrating that older adults have thicker MS capsules [ 11 ]. Moreover, these findings are consistent with those of some studies that highlighted the role of the collagens in various diseases and tissues [ 21 , 22 , 23 ]. Parkes et al [ 21 ] reported the prominent role of collagen and HA in the ECM of ovaries, suggesting their crucial activity for ovarian homeostasis, possibly through signaling events or tissue micromechanism.…”
Section: Discussionsupporting
confidence: 92%
“…Cell behavior is profoundly affected by the environment in which they live, thus the aging of the ECM is central to understanding age-related changes [ 17 ]. Nowadays, ECM’s role has been highlighted in different diseases and tissues [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…50 Recently, the TT genotype has also been reported to be associated with increased risk of TMJ displacement (Figure 2). 51 Although the rs12722 polymorphism was not associated with non-contact soft tissue injuries (Table S3 and Figure 2), 52,53 other studies have reported the COL5A1 T allele is associated with slower post exercise-induced muscle damage recovery 34 and the TT genotype is associated with the severity but not the incidence of musculoskeletal injuries in professional soccer players. 54…”
Section: Tennis Elbow and Other Musculoskeletal Injuriesmentioning
confidence: 89%
“…Furthermore, condylar resorption after surgical mandibular advancement may be associated with coexisting disc displacement [ 22 , 23 ]. Recently, Dalewski et al [ 24 , 25 ] have explored the genetic susceptibility to anterior disc displacement without reduction (ADDwoR) in European Caucasians and reported that the COL5A1 and ESR1 receptors are a risk factor for ADDwoR, indicating the possibility of genetic susceptibility to ICR. Advancing the mandible in a patient with anteriorly displaced discs causes the discs to remain displaced, as the condyles move toward the superoposterior position in the glenoid fossa due to postsurgical soft tissue tension [ 23 ].…”
Section: Discussionmentioning
confidence: 99%